The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

La pensée feministe noire : savoir, conscience et politique de l'empowerment - Hill Collins, Patricia (Les éditions du remue-ménage, 2016)
Confrontées à une société sexiste et raciste qui leur impose des images stigmatisantes d’elles-mêmes, les femmes noires des États-Unis n’en ont pas moins une longue histoire de résistances. Dans cet essai incontournable enfin traduit en français, Patricia Hill Collins nous offre une synthèse impressionnante de cette tradition d’oppression et de militantisme. La pensée féministe noire puise autant dans la littérature, les récits de vie, l’histoire militante, la philosophie sociale et politique, la sociologie critique que dans la culture populaire. Elle nous incite à penser non seulement les oppressions enchevêtrées, mais aussi les luttes passées et à venir. Ce livre donne accès à un savoir profondément ancré dans l’expérience irréductible des Africaines-Américaines; un savoir essentiel pour qui se préoccupe de justice sociale et pour un féminisme véritablement inclusif.
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; com5170; cours; cycles supérieurs; discipline; fem1000; fem3300; fem7000; féminismes noirs; har4600; incontournable; intersectionnalité; justice sociale; militance; pol4212; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie; états-unis

The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes

De l'analogie à l'articulation : théoriser la différenciation sociale et l'inégalité complexe - Bilge, Sirma (L'Homme & la Société, 2010)
L’intersectionnalité semble être devenue le trope dominant pour parler de l’articulation des rapports sociaux structurants, et des identités/inégalités sociales multiples. S’agit-il de la dernière tendance terminologique dans la recherche et l’action féministes aux prises avec l’injonction de tenir compte de la « diversité » ou sommes-nous en face d’une nouvelle manière de penser les divisions sociales, d’une nouvelle épistémologie du pouvoir et de la domination ? L’article retrace la genèse du paradigme intersectionnel en en distinguant les théorisations principales et en s’attardant sur leurs potentialités et leurs limites respectives.
Keywords: 2000 à aujourd'hui; approches et analyses; cours; discipline; fem3300; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; sciences humaines; épistémologie